Adaptaciones fisiológicas en algunas especies de mangles (1990)
The role of manitol and proline on the osmotic balance of Aegiceras corniculatum, Aegialitis annul ata and Laguncularia racemosa were studied. Mangrove plants were grown in hydroponic cultures for several years before using them for the experiments described here. The plants grown in different salt concentrations and "shock" treatments were divided in their parts and the ion concentrations of the low molecular weight compounds of each part were analysed. High concentrations of osmotic compounds were found in all plant parts. The role of mannitol, as an overall osmotic compound, is discussed.